Magnetically responsive composites: Electron beam assisted magnetic nanoparticle arrest in gelatin hydrogels for bioactuation - Deuflhard, Marie; Eberbeck, Dietmar; Hietschold, Philine; Wilharm, Nils; Mühlberger, Marina; Friedrich, Ralf P.; Alexiou, Christoph; Mayr, Stefan G. (Physical Chemistry Chemical Physics, 2019)
As emerging responsive materials, ferrogels have become highly attractive for biomedical and technical applications in terms of soft actuation, tissue engineering or controlled drug release. In the present study, bioderived ferrogels were fabricated and successfully deformed within moderate, heterogeneous magnetic fields. Synthesis was realized by arresting iron oxide nanoparticles in porcine gelatin by introduction of covalent crosslinks via treatment with energetic electrons for mesh refinement. This approach also allows for tuning thermal and mechanical stability of the gelatin matrix. Operating the bioferrogel in compression, magnetic forces on the nanoparticles are counterbalanced by the stiffness of the hydrogel matrix that is governed by a shift in thermodynamic equilibrium of swelling, as derived in the framework of osmosis. As gelatin and iron oxide nanoparticles are established as biocompatible constituents, these findings promise potential for in vivo use as contactless mechanical transducers.
CRIS-Team Scopus Importer:2019-07-23